Antioxidant Effects of Red Fruit Oil on MMP-1 Gene Expression and Malondialdehyde Levels on Skin Exposed to UVB Rays - Monita Sugianto; Achadiyani Achadiyani; Gaga Irawan Nugraha (Cell and BioPharmaceutical Institute, 2019)
Background: Chronic exposure ultraviolet (UV)-B radiation causes reactive oxygen species (ROS) formation. Furthermore, ROS will induce the formation of malondialdehyde and increase matrix metalloproteinase (MMP)-1 expression. One strategy against the free radicals effects is by consuming antioxidants. This study aims to analyze the antioxidants effect of red fruit oil (RFO) on MMP-1 expression and malondialdehyde levels due to exposure to UVB rays.Materials and Methods: Thirty male Wistar rats were divided into 5 groups. The P0 group was not given treatment, the P1 group was only exposed to UVB light, the P2 group was exposed to UVB light and given 0.5 mL/200 g body weight (BW) of RFO, the P3 group was exposed to UVB light and given 1 mL/200 g BW of RFO, and group P4 exposed to UVB rays and given 2 mL/200 g BW of RFO. Experimental animals would be examined for MMP-1 expression and malondialdehyde level. RFO would be identified with β-carotene and tocopherol content.Results: Beta-carotene and tocopherol were detected in RFO. RFO reduced significantly MMP-1 expression (p<0.05) in P2 group (0.73±1.27), P3 group (0.63±0.95), P4 group (9.56±20.97) compared group P1 (48.07±65.58). However, RFO did not reduce malondialdehyde levels (p>0.05).Conclusion: Our research demonstrates RFO containing tocopherol and β-carotene can reduce the MMP-1 expression, but does not affect malondialdehyde levels due to exposure to UVB rays. An effective dose that can reduce malondialdehyde levels and MMP-1 expression is 1 mL/200 g BW.Keywords: red fruit oil, antioxidant, skin, MMP-1 expression, malondialdehyde, UVB rays, photoaging